Artificial intelligence-driven innovation in English language education: a thematic literature review and conceptual framework for Indonesian EFL context - Imelda Darmayanti Manurung; Faisal Rahman Dongoran; Tengku Winona Emelia; Lia Khalisa (Indonesian Journal Education, 2026)
The use of Artificial Intelligence (AI) in English as a Foreign Language (EFL) education has expanded rapidly, transforming learning, assessment, teacher professional development, and educational governance. However, existing studies predominantly examine these dimensions independently, leaving a lack of an integrated conceptual framework to explain AI implementation as a comprehensive educational ecosystem. This study aims to synthesize recent research on AI in EFL education, identify emerging themes, and propose the AI-Integrated EFL Innovation Framework (AIEIF). A Thematic Literature Review was conducted on twelve peer-reviewed international articles published between 2024 and 2025. Data were analyzed through open coding, category development, and thematic synthesis to identify recurring conceptual patterns across studies. The analysis generated five interrelated themes: AI-Supported Student Learning, AI for Teacher Professional Development, AI-Based Assessment Innovation, AI Leadership and Educational Governance, and Challenges and Future Directions. The findings indicate that effective AI implementation depends on the integration of adaptive learning, teacher capacity building, data-driven assessment, institutional leadership, and governance while addressing ethical, technological, policy, and cultural considerations. The proposed AIEIF offers a human-centered conceptual framework that advances AI integration in EFL education and provides a foundation for future empirical research, educational policy, and sustainable AI implementation, particularly in the Indonesian context.